2015
DOI: 10.1596/1813-9450-7491
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Value Added in Exports: Theory and Firm Evidence from China

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
106
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 11 publications
18
106
0
4
Order By: Relevance
“…Despite different approaches existing, the point of capturing the participation in GVCs’ index at micro firm level, is to quantify the FVA in the productive process of each firm. According to the methods of Zhang, Chen, and Liu (), and Kee and Tang (), we use the data from the CCTS database to measure the participation in GVCs in two steps.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Despite different approaches existing, the point of capturing the participation in GVCs’ index at micro firm level, is to quantify the FVA in the productive process of each firm. According to the methods of Zhang, Chen, and Liu (), and Kee and Tang (), we use the data from the CCTS database to measure the participation in GVCs in two steps.…”
Section: Empirical Analysismentioning
confidence: 99%
“…It is worth noting that the findings for Mexico are the opposite to those for China. For instance, Kee and Tang (2012) measured the evolution of China's domestic value added in processing exports between 2000 and 2006 and found that this share has been increasing from 35% to 49%. The authors show that this increasing trend is driven by within-firm substitution of imported materials with domestic materials and not by changes in the composition of firms or industries.…”
Section: Discussionmentioning
confidence: 99%
“…To analyse whether the decline in the overall share of domestic value added is due to within-firm reduction in the share of domestic value added or to changes in the establishment's participation in total processing exports (including firm entry and exit), we follow Kee and Tang (2012) and estimate the following equation:…”
Section: Empirical Analysismentioning
confidence: 99%
“…Combining customs and industrial enterprise data involves very complicated technical details. Based on previous methods, we strive to match the two databases accurately and comprehensively (Kee et al, 2013;Feenstra et al, 2014;Ma et al, 2014;Feng et al, 2016). The third set of data is China's import tariff data obtained from the United Nations Conference on Trade and Development (UNCTAD) Trade Analysis Information System (TRAINS).…”
Section: Datamentioning
confidence: 99%